2017
DOI: 10.1001/jamapediatrics.2017.2536
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Price Differentials With Infant Mortality in 23 European Union Countries

Abstract: IMPORTANCE Raising the price of cigarettes by increasing taxation has been associated with improved perinatal and child health outcomes. Transnational tobacco companies have sought to undermine tobacco tax policy by adopting pricing strategies that maintain the availability of budget cigarettes.OBJECTIVE To assess associations between median cigarette prices, cigarette price differentials, and infant mortality across the European Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…Evidence from HICs has shown that smoke-free policies have led to reductions in adverse maternal and child health outcomes [61,62]. Additionally, a recent study in 23 European Union countries found that increases in the median price of cigarettes were associated with reductions in infant mortality between 2004 and 2014, probably because of reductions in smoking and secondhand smoke exposure [63]. However, more research is needed to develop and evaluate interventions to address SHS exposure during pregnancy in LMICs in the context of cultural and socioeconomic barriers [4].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from HICs has shown that smoke-free policies have led to reductions in adverse maternal and child health outcomes [61,62]. Additionally, a recent study in 23 European Union countries found that increases in the median price of cigarettes were associated with reductions in infant mortality between 2004 and 2014, probably because of reductions in smoking and secondhand smoke exposure [63]. However, more research is needed to develop and evaluate interventions to address SHS exposure during pregnancy in LMICs in the context of cultural and socioeconomic barriers [4].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco prices are most sensitive among younger and lower income people. Data from over 53 million births across 24 European countries showed that a price increase of $1.18 per pack of cigarettes was associated with a decline of 0.23 deaths per 1,000 live births in the same year and 0.16 deaths per 1,000 live births the following year (Filippidis, Laverty, Hone, Been, & Millett, ). Relief of stressful living conditions, directly linked to poverty and racism, would also be important to recognize.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing tobacco prices, a strategy associated with an immediate marked decrease in infant mortality in Europe (level 5). 37 2. Ending racial bias in the health care system that undermines breastfeeding and leads to poor maternal and infant outcomes(level 2) 38,39 (level 3).…”
Section: Place Infants To Sleep Away From Secondhand Smoke Andmentioning
confidence: 99%